Center-Commissioned External Review (CCER) Poverty, Health and Nutrition Division (PHND) - Glewwe, Paul; Levine, Ruth (International Food Policy Research Institute, 2009)
This report presents findings of a one-week Center-Commissioned External Review (CCER) of the Poverty, Health and Nutrition Division (PHND) of the International Food Policy Research Institute. Overall, the review found that the division is making major contributions to global knowledge and informed policy through its high-quality empirical microeconomic, nutrition, program evaluation and other research. While there is scope for improvement and enhancement at the margins, and value in working toward a situation in which more unrestricted resources are available to pursue important research topics, overall the review found that the division is healthy, well managed, and likely to prosper and to continue to make important contributions to research on development in the years to come.